Bureaucracy Reform through Transformation of Public Services at the Department of Investment and One Door Integrated Services (Case Study in the City of Palangka Raya, Gunung Mas Regency and Central Kalimantan Province) - Hera Nugrahayu; Sadu Wasistiono; Hyronimus Rowa; Sampara Lukman (Budapest International Research and Critics University, 2022)
Inadequate information technology facilities and infrastructure to support public services in DPMPTSP. In addition, various local legal products have not clearly accommodated the role of Dayak customary institutions and local wisdom values in public services, even though they have acknowledged the structure of Dayak customary institutions in writing as stated in the Central Kalimantan Provincial Regulation Number 16 of 2008 concerning Institutions. Dayak Customs in Central Kalimantan, Central Kalimantan Governor Regulation Number 27 of 2019 concerning Utilization of Peat Swamp Land through Local Wisdom. Regional Regulation of Gunung Mas Regency Number 33 of 2011 concerning Indigenous Dayak Institutions in Gunung Mas Regency, and Regional Regulation of Palangka Raya City Number 15 of 2009 concerning Indigenous Dayak Institutions in Palangka Raya City. This study was designed using a qualitative descriptive research method. This study is intended to analyze the transformation that occurs in public services at DPMPTSP in Central Kalimantan Province. This is done as an effort to find the truth with critical thinking about a problem that occurs and the innovation that has been carried out. Based on the results of the research above, the authors can explain that the performance of public services is influenced by the external environment in the form of hospitality (munificence), complexity and dynamism as well as regularity. Second, influenced by organizational characteristics such as planning, leadership, culture and human resources of the apparatus. Third, influenced by organizational strategy in the form of innovation, partnership and learning. The researcher will describe the transformations found in the components of the theory in question.